Transverse transfixing wounds of the mediastinum - Delbene, Roberto; Pomi, Jorge; Pérez Penco, Ernesto; Maggiolo, José; Chifflet, Juan; Martínez, José Luis (Cirugía del Uruguay, 1997)
A report ís provided of 10 cases of transverse transfixiant wounds (TTIF) treated over a 15 year period.